2011
DOI: 10.1111/j.1439-0426.2011.01868.x
|View full text |Cite
|
Sign up to set email alerts
|

Life history traits of Aphanius ginaonis Holly, 1929 (Cyprinodontidae) and potential risks of extinction in the Geno hot spring (Iran) population

Abstract: This study presents some traits of the Aphanius ginaonis life history in the Geno hot spring and explains the potential risks of its extinction. Sampling was from March 2009 to February 2010. A total of 61 males and 71 females were measured (total length) and weighed, with data on reproductive biometry also taken. Growth parameters were determined in addition to weight-length relationships: W (t) = 0.012TL 3.42 , R 2 = 0.96 for females and W (t) = 0.0101TL 3.38 , R 2 = 0.94 for males. A. ginaonis females showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The maximum age of Aphanius species varies between 2+ and 7+ (Leonardos and Sinis, 1999;Keivany and Soofiany, 2004;Gu¨c¸lu¨et al, 2007;Kamal et al, 2009;Oliva-Paterna et al, 2010;Golmoradizadeh et al, 2011), and longevity of the A. danfordii can be as much as five years in the Hirfanli Reservoir. The sex ratio found in this study is also similar to those found in many studies conducted on Aphanius (Leonardos and Sinis, 1999;Gu¨c¸lu¨and Ku¨c¸u¨k, 2008;Kamal et al, 2009;Oliva-Paterna et al, 2010;Golmoradizadeh et al, 2011). As in many of the studies, females were dominant in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum age of Aphanius species varies between 2+ and 7+ (Leonardos and Sinis, 1999;Keivany and Soofiany, 2004;Gu¨c¸lu¨et al, 2007;Kamal et al, 2009;Oliva-Paterna et al, 2010;Golmoradizadeh et al, 2011), and longevity of the A. danfordii can be as much as five years in the Hirfanli Reservoir. The sex ratio found in this study is also similar to those found in many studies conducted on Aphanius (Leonardos and Sinis, 1999;Gu¨c¸lu¨and Ku¨c¸u¨k, 2008;Kamal et al, 2009;Oliva-Paterna et al, 2010;Golmoradizadeh et al, 2011). As in many of the studies, females were dominant in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…1). Sexual size dimorphism is well known in this genus, with females attaining a larger size than males (Gandolfi et al ., 1991;Leonardos & Sinis, 1999;Doadrio et al ., 2002;Golmoradizadeh et al ., 2012). The breeding system is based on an intense male-male competition for the access of single females, which are led to spawn on algal mops or other substrata (Gandolfi et al ., 1991;Malavasi et al ., 2010).…”
mentioning
confidence: 99%